فعالية برنامج تربية اختيارات قائم على التغيير المفهومي في تعديل التصورات البديلة حول المشروع الشخصي لدى تلاميذ السنة الثالثة متوسط - علاق, مباركة (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2019)
هدفت الدراسة إلى الكشف عن مد فعال ة برنامج تر ة اخت ارات قائم على التغیر المفهومي في تعدیل التصورات البدیلة حول المشروع الشخصي لد تلامیذ السنة الثالثة متوس. و سعى البرنامج إلى تعدیل التصورات البدیلة حول المشروع الشخصي، والتي تعبر عن المعرفة التي یتلقاها التلمیذ من المح الاجتماعي(الأسرة، المدرسة، المجتمع، جماعة الرفاق....) حول ذاته وحول مح طه الدراسي والمهني، وغال ا ما تكون خاطئة أوغیر دق قة. و استخدام خطوات التغیر المفهومي یتم إحداث حالة من اللاتوازن المعرفي بین تصور ن لمساعدة التلامیذ على الانتقال إلى التصور الجدید والذ ساعدهم على التعرف الموضوعي لذواتهم ولمح طهم الدراسي والمهني. و الاعتماد على المنهج التجر بي ذو التصم م الق اس القبلي وال عد لمجموعتین إحداهما ضا طة والأخر تجر ب ة تم إجراء الدراسة على عینة مقدرة بـ 30 تلمیذا وتلمیذة مقسمین على مجموعتین: مجموعة تجر ب ة تشمل 15 تلمیذا ومجموعة ضا طة تشمل 15 تلمیذا من تلامیذ السنة الثالثة متوس. و استخدام أدوات جمع الب انات التي تمثلت في مق اس التصورات البدیلة حول المشروع الشخصي (إعداد ال احثة) و استخدام الأسالیب الإحصائ ة المتمثلة في اخت ار"ت" لدلالة الفروق بین المتوسطات تم التوصل إلى النتائج التال ة: ـ توجد فروق ذات دلالة إحصائ ة بین متوس أفراد المجموعة التجر ب ة وأفراد المجموعة الضا طة على مق اس التصورات البدیلة حول المشروع الشخصي في الق اس ال عد. ـ توجد فروق ذات دلالة إحصائ ة بین متوس أفراد المجموعة التجر ب ة وأفراد المجموعة الضا طة على مق اس التصورات البدیلة حول المشروع الشخصي(تصورات بدیلة حول الذات، تصورات بدیلة حول المح الدراسي، تصورات بدیلة حول المح المهني) في الق اس ال عد. ـ توجد فروق ذات دلالة إحصائ ة بین الق اس ال عد والق اس التت عي للمجموعة التجر ب ة لصالح الق اس ال عد في مق اس التصورات البدیلة حول المشروع الشخصي. ج و ناء عل ه تم التحق من فعال ة برنامج تر ة اخت ارات قائم على التغیر المفهومي في تعدیل التصورات البدیلة حول المشروع الشخصي لد تلامیذ السنة الثالثة متوس. و التالي تم التأكید على ضرورة تفعیل مثل هذه البرامج ل تسب التلمیذ تصورات دق قة وموضوع ة حول ذاته وحول مح طه الدراسي حتى یتسنى له ص اغة مشروع شخصي وف أسس ومعاییر صح حة. د Abstract The aim of the study was to identify the effectiveness of a selection program based on conceptual change in modifying the alternative perceptions of the personal project among the third-year preparatory students. Based on the experimental study design with pre and post measurement a sample of 30 students males and femaleswas divided into two groups: an experimental group consisting of 15 students and a control group of 15 students among third-year preparatory students. The program seeks to modify alternative perceptions about the personal project, that reflect the knowledge received by the student from the social environment (family, school, community, peers ....) about himself and his academic and professional surrounding, and which are very often wrong or inaccurate. Using the steps of conceptual change, a state of cognitive imbalance is created between two perceptions to help students move towards this new perception, which helps them to objectively identify themselves and their academic and professional environment. Using the data collection tools, represented in the scale of alternative perceptions about the personal project prepared by the researcher and using the statistical methods of T test to determine the differences between the means, the following results were obtained: - There are statistically significant differences between the mean of the experimental group members and the mean of control group members on the scale of alternative perceptions about the personal project in post measurement. - There are statistically significant differences between the mean of the experimental group members and the mean of control group members on the scale of alternative perceptions about the personal project (alternative perceptions of the self, alternative perceptions of the academic environment, alternative perceptions of the occupational environment) in post measurement. - There are statistically significant differences between the post measurement and the sequential measurement of the experimental group for post measurement. Accordingly, the effectiveness of theselection program based on conceptual change in modifying the alternative perceptions of the personal project among third-year preparatory students has been verified. Therefore, it was emphasized the necessity of activating such programs so that students can have accurate and objective perceptions of themselves and their academic environment so that they can formulate a personal project based on sound principles and criteria.
أطروحة دكتوراه تخصص ارشاد وتوجيه في العلوم الإجتماعية و الإنسانية
Keywords: الثاني:تربية الاختيارات كإطار لبناء المشروع الشخصي/التغیر المفهومي/التصورات البدیلة; The second: raising choices As a framework for building a personal project / conceptual change / alternative perceptions